2018
DOI: 10.29202/nvngu/2018-5/1
|View full text |Cite
|
Sign up to set email alerts
|

Physical conditions of the ‘light’ core formation and thermonuclear heat source deep inside the earth

Abstract: Purpose. Experimental research into the physical model of the Earth's core formation in the center of gas-dust spiral vortex and numerical assessment of the physical conditions associated with the development of thermonuclear reactions in the Earth's core. Methodology. Analysis of the main points of conventional conceptions, their principal merits and drawbacks which delineate their potential possibilities. Experimental studies implementing shock-wave treatment of porous materials in cylindrical containers. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Such vortex structures are char acterized by differential distribution of matter in vortex spirals according to density: lighter components (hydrogen, helium etc.) were mostly concentrated in the center, while heavier ones, like dust particles, were located on the vortex periphery [84,85]. Diamond particles, relics of protoplanetary matter, having "settled" in the Earth mantle, passed through the stag es of adaptation and conservation.…”
Section: A Ke Rs T E Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Such vortex structures are char acterized by differential distribution of matter in vortex spirals according to density: lighter components (hydrogen, helium etc.) were mostly concentrated in the center, while heavier ones, like dust particles, were located on the vortex periphery [84,85]. Diamond particles, relics of protoplanetary matter, having "settled" in the Earth mantle, passed through the stag es of adaptation and conservation.…”
Section: A Ke Rs T E Rtmentioning
confidence: 99%
“…The authors of [61,84,85] suggested that relic diamond particles could be found in other bodies of the Solar Sys tem, e. g. meteorites [86]. This idea was later (1987) proved in the research [1].…”
Section: A Ke Rs T E Rtmentioning
confidence: 99%
“…The method for forming a plane detonation wave is reliable. Evidence is a number of positive experimental results obtained during the formation of plane shock waves in the material under study directly by a plane detonation wave front at an angle of 0° relative to the surface of the material facing the striker [33,34], or by a detonation wave front sliding at an angle of 90° to the generatrix of the cylinder surface [35], or by the impact of a fl at plate accelerated by the products of the PEC explosion [36], including in problems of studying the nature of the fl ow of matter behind the front of the bow shock [37].…”
mentioning
confidence: 99%